DIALEKTIKA RADIKALISME DAN ANTI RADIKALISME DI PESANTREN - Kusmanto, Thohir Yuli; Fauzi, Moh Fauzi; Jamil, M Mukhsin (WALISONGO, 2015)
Any effort opoosing toward any form of radicalism is a part of the reactions to antiradicalism.The spirit of anti-radicalism emerged as part of the peoples resistance.Radicalism and anti-radicalism was dialectically interrelated. Although both areparadoxical, but always be united. Dialectic of radicalism and anti-radicalism interesting isonce it was observed in boarding school life. The phenomena of Islamic radicalism isoften associated with Islamic boarding schools in Indonesia. Some communitiesunderstood that the growing radicalism came from Islamic boarding schools. This viewwas based on the the many actors of violent Islamic radicalism were the alumni ofboarding school. The reality may be true in certain cases, but they may not be generalized.This study explored the data on the perspective of Islamic boarding schools on thediscourse and praxis of radicalism and anti radicalism and resistance patterns. The researchresults showed that the community of Islamic boarding schools rejected, oppossed andactively built the spirit of anti radicalism that was implemented in several patterns. Thefindings of these research was a synthesis of the thesis which had become the publicdiscourse about radicalism and Islamic boarding school.***Upaya menentang segala bentuk radikalisme merupakan bagian dari reaksi antiradikalisme. Semangat anti radikalisme muncul sebagai bagian dari resistensimasyarakat. Radikalisme dan anti radikalisme saling berkaitan secara dialektis. Meskipunkeduanya merupakan sesuatu yang paradoks, namun selalu menyatu. Dialektikaradikalisme dan anti radikalisme menarik ketika dilihat dalam kehidupan pesantren.Fenomena radikalisme Islam seringkali dihubungkan dengan masyarakat pesantren diIndonesia. Beberapa kelompok masyarakat memahami radikalisme tumbuh daripesantren. Pandangan tersebut didasari oleh banyaknya pelaku radikalisme Islamdalam bentuk kekerasan alumni pesantren. Realitas tersebut bisa jadi benar dalamkasus tertentu, tetapi tidak bisa digeneralisasi. Penelitian ini berupaya menggali datapandangan pesantren tentang wacana dan praksis radikalisme dan anti radikalismeserta pola resistensinya. Hasil penelitian menunjukkan bahwa masyarakat pesantrenmenolak, menentang dan aktif membangun spirit anti radikalisme yang diwujudkandalam beberapa pola. Temuan penelitian tersebut merupakan sintesis dari tesis yangselama ini menjadi wacana masyarakat tentang radikalisme dan pesantren.